Neutrophil-activating therapy for the treatment of cancer - Linde, Ian L.; Prestwood, Tyler R.; Qiu, Jingtao; Pilarowski, Genay; Linde, Miles H.; Zhang, Xiangyue; Shen, Lei; Reticker-Flynn, Nathan E.; Chiu, David Kung-Chun; Sheu, Lauren Y.; Van Deursen, Simon; Tolentino, Lorna L.; et al. (Cancer cell, 2023)
Despite their cytotoxic capacity, neutrophils are often co-opted by cancers to promote immunosuppression, tumor growth, and metastasis. Consequently, these cells have received little attention as potential cancer immunotherapeutic agents. Here, we demonstrate in mouse models that neutrophils can be harnessed to induce eradication of tumors and reduce metastatic seeding through the combined actions of tumor necrosis factor, CD40 agonist, and tumor-binding antibody. The same combination activates human neutrophils in vitro, enabling their lysis of human tumor cells. Mechanistically, this therapy induces rapid mobilization and tumor infiltration of neutrophils along with complement activation in tumors. Complement component C5a activates neutrophils to produce leukotriene B4, which stimulates reactive oxygen species production via xanthine oxidase, resulting in oxidative damage and T cell-independent clearance of multiple tumor types. These data establish neutrophils as potent anti-tumor immune mediators and define an inflammatory pathway that can be harnessed to drive neutrophil-mediated eradication of cancer. [Display omitted] •Therapeutically activated neutrophils infiltrate and eradicate multiple tumor types•Intratumoral TNF + anti-CD40 + anti-tumor antibodies induce an inflammatory cascade•Neutrophil C5AR1 signaling stimulates LTB4 release, driving ROS production via XO•Neutrophil-mediated oxidative damage drives T cell-independent tumor clearance Linde et al. describe a cancer therapy that activates neutrophils to infiltrate and eradicate tumors and reduce metastatic seeding. The authors elucidate the responsible mechanism, which involves complement component C5a, leukotriene B4, and reactive oxygen species, and demonstrate the potential of harnessing neutrophils through inflammatory activation to drive tumor clearance.